China and Russian Federation: Policy From 1991 to 1999 - Mieczysław Sprengel (Восточная Азия: факты и аналитика, 2020)
1989 was a time of a breakthrough for many countries and countries around the world. The symbolic fall of the Berlin Wall and the libertarian events in Poland have led to a coup in the authoritarian rule of many countries. Democracy and the rule of law began to function in countries that were overwhelmed by totalitarian regimes after World War II. These processes have also affected Russia and China. In 1990– 1991 Mikhail Gorbachev was the only president of the Soviet Union and author of the perestroika, which is a major change in present-day Russia. The events of the 17th of April, 1989 in China in Tiananmen Square also show the aspirations of students and society to democratize and economic development and the fight against corruption. The time of the last decade of the 20th century is extremely interesting for historians and researchers and raises many interesting questions. The questions are about how in the new political and economic reality have the countries affected by these changes found themselves? And how did the relationship on the new political scene of the world have come into place? Two very important countries Russia and China will be particularly examined in this article. Due to their importance and population potential and resource efficiency, it is important to look for important vectors of change. These countries are also important in geopolitics, so it is important to examine them in their relations with the United States. Despite the fact that the years 1991–1999 are characterised by constructive partnerships and strengthening cooperation between Russia and China, it is worth looking at these relations in a broader perspective.